HISTORY OF ECONOMIC TRADE IN ISLAM AND ITS INFLUENCE ON INTERNATIONAL RELATIONS POLICY IN THE ARABIAN PENINSULA - Yudha, Gesit Yudha; Aziz, Abdul; Arini, Isti (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Arabian Peninsula has a long history of trade from pre-Islamic times to the Islamic era. The arrival of Islam brought economic principles that emphasize justice and social responsibility in trade. Sharia-driven trade practices help expand trade networks, strengthen political stability, and influence international relations. The aim of this research is to explore and analyze how economic principles in Islam shaped and directed the development of trade on the Arabian Peninsula and the significant impact they had on international relations at that time. The research method in this study uses a literature study approach to collect, analyze and synthesize relevant information. This research will begin by searching various secondary sources, including history books, academic journal articles, and historical documents that discuss economic trade in Islam as well as political and social developments on the Arabian Peninsula. These sources will be selected based on their credibility and relevance to the research topic. The results of this research are that trade has played a central role in the history of the Arabian Peninsula, from pre-Islamic times to the Ottoman Empire. Cities such as Mecca and Medina have become vital trade centers, influencing the economy, politics, society and culture. Trade forms the foundation for international relations, enriches economies, and influences diplomacy and cultural development.